2024
DOI: 10.1021/acsanm.3c05427
|View full text |Cite
|
Sign up to set email alerts
|

Review of Polymeric Nanocomposites for Photocatalytic Wastewater Treatment

Shaon Dey,
Kalipada Manna,
Padmapani Pradhan
et al.

Abstract: The continuous upsurge in water pollution caused by harmful organic and inorganic contaminants has led to a shortage of nontoxic, clean water and effective waste management. Therefore, it is crucial to establish an eco-friendly approach using sustainable, biodegradable, and recyclable materials to treat the wastewater. In this regard, photocatalysts are highly effective for mitigating water pollution to a certain degree through an energy-efficient and greener approach. Among various photocatalysts, polymeric n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 227 publications
0
1
0
Order By: Relevance
“…Nevertheless, to overcome some inherent flaws of the nanocomposites in photocatalytic performance, including the high recombination rate of the photoexcitons, the short lifespan of the photogenerated charge carriers, the limited absorption of visible light, and the delayed electron transport, it has become accustomed to characterize the trend of the formation of solid-state-mediated Z-schemes over the common Z-scheme heterostructures. Therefore, a noble metal mediator-based ternary Z-scheme heterojunction with electron channelizers for rapid charge carrier separation efficiency has been selected as an efficient photocatalyst for multiple pollutant degradation under visible light . Recently, a series of reports revealed that the plasmonic silver (Ag 0 )-based Z-scheme system significantly improves the photocatalytic activity by generating an induced local electric field under visible light, owing to the excellent electron conductivity and surface plasmon resonance (SPR) effect of plasmonic silver (Ag 0 ) or metallic nanosilver (AgNP). , …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to overcome some inherent flaws of the nanocomposites in photocatalytic performance, including the high recombination rate of the photoexcitons, the short lifespan of the photogenerated charge carriers, the limited absorption of visible light, and the delayed electron transport, it has become accustomed to characterize the trend of the formation of solid-state-mediated Z-schemes over the common Z-scheme heterostructures. Therefore, a noble metal mediator-based ternary Z-scheme heterojunction with electron channelizers for rapid charge carrier separation efficiency has been selected as an efficient photocatalyst for multiple pollutant degradation under visible light . Recently, a series of reports revealed that the plasmonic silver (Ag 0 )-based Z-scheme system significantly improves the photocatalytic activity by generating an induced local electric field under visible light, owing to the excellent electron conductivity and surface plasmon resonance (SPR) effect of plasmonic silver (Ag 0 ) or metallic nanosilver (AgNP). , …”
Section: Introductionmentioning
confidence: 99%